Efficacy of fermented foods for the prevention and treatment of bacterial vaginosis and vulvovaginal candidiasis - Akpınar, Aslı; Markiewicz, Lidia Hanna; Harsa, Hayriye Şebnem; Paveljšek, Diana; Domínguez-Soberanes, Julieta; Agirbasli, Zeynep; Naziri, Eleni; El Jalil, Mounaim Halim; Bouchaud, Gregory; Salminen, Seppo; Savary-Auzeloux, Isabelle; Humblot, Christèle; et al. (Frontiers in Nutrition, 2025)
Vaginal function in healthy women is closely associated with a lactobacilli-dominated microbiome. Among the most common conditions arising from dysbiosis are bacterial vaginosis (BV) and vulvovaginal candidiasis (VVC). While the efficacy of oral probiotics for the treatment of BV and VVC is well documented, the role of consuming fermented foods remains underexplored. This systematic review aims to present a systematic evaluation of the potential role of fermented foods in the prevention and treatment of BV and VVC and establish the extant research gap between the realm of the clinical sciences and the field of food science and technology. For this purpose, under the guidance of COST Action CA20128—Promoting Innovation of Fermented Foods (PIMENTO), a systematic literature review was conducted in two phases. PubMed, Scopus, and Cochrane databases were used for Phase I to analyze articles on human trials and observational studies where the intervention/exposure involved oral consumption of fermented food. In Phase II, a two-step search strategy was employed: (i) identifying microorganisms with demonstrated clinical efficacy in managing BV and VVC, and (ii) reviewing food science literature where these strains are utilized for fermentation. It was observed that 87% of the food starter applications exploited only two of the 54 efficacious strains identified through clinical studies, namely Lactobacillus rhamnosus GG and Lactobacillus acidophilus LA-5. Findings underscore the potential of fermented foods as carriers for beneficial microorganisms and their relevance in supporting vaginal health. This review contributes to a deeper understanding of the interplay between nutritional consumption of viable probiotic strains and their importance in immunomodulation, highlighting the need for more integrated research efforts across disciplines. Future research aimed at filling this gap will enable informed clinical decisions and dietary recommendations.